La recherche des nombres caracteristiques pour le Système d’une classe d’équations differentielles à coefficients périodiques. II - Golokvosčius, P. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Голоквосчюс. Отыскание характеристических чисел решений одного класса систем дифференциальных уравнений с периодическими коэффициентами. Часть II P. Golokvosčius. Vienos klasės diferencialinių lygčių su periodiniais koeficientais sistemų sprendinių charakteringųjų skaičių radimas, II dalis